Phylogenomics and female reproductive morphology reframe the classification of the Halymeniales (Rhodophyta) - Frederik Leliaert; Showe-Mei Lin; Conxi Rodríguez-Prieto; John M. Huisman; Maggie M. Reddy; Roberta D’Archino; Gary Saunders; Felix Powrie; Jeffery R. Hughey; Paul W. Gabrielson; Sofie D’hondt; Kenny Bogaert; et al. (Molecular Phylogenetics and Evolution, 2026)

Low-temperature plasma priming enhances nutrient removal and astaxanthin production in Haematococcus pluvialis: Transcriptomic responses during controlled aquaculture wastewater cultivation - Zuo Lin; Chen Zhu; Wang Fen; Ha Thanh Dong; Takuji W. Tsusaka; Nimish Devendra Dhuri; Jiang Yelin; Zhou Xiang; Krishna R. Salin (Bioresource Technology, 2026)

Correction: The potent human CAR activator CITCO is a non-genotoxic hepatic tumour-promoting agent in humanised constitutive androstane receptor mice but not in wild-type animals - C. J. Henderson; A. W. McLaren; A. K. MacLeod; D. Lin; A. R. Cameron; L. R. Chatham; J. Moggs; F. Inesta‑Vaquera; John P. Thomson; Richard R. Meehan; P. Chakravarty; M. Schwarz; et al. (Archives of Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Plasticity and regional heterothermy of upper thermal tolerance in the ring-necked snake - Christian L. Cox; Kelly Lin Wuthrich; Dareen Aloudeh; Samuel J. Baker; Anna G. Climo; Alexa F. Gross; Christian W. Kizer; Zoe M. Korff; Oscar Melendez Vera; Veronica Y. Silva; Alexis M. Spans; Grace R. Thilenius; et al. (Journal of Thermal Biology, 2026)